50 μJ Femtosecond Laser System Based on Strictly All-Fiber CPA Structure - Feng Li; Zhi Yang; Wei Zhao; Qianglong Li; Xin Zhang; Xiaojun Yang; Wei Zhang; Yishan Wang (IEEE Photonics Journal, 2016)
We demonstrate a strictly all-polarization maintaining, all-fiber chirped pulse amplification of ultrashort pulses. Pulses with the duration of 933 fs and energy as high as 50 μJ are achieved at 200 kHz repetition rate in a compact size. The variations of the spectra and pulse widths as functions of the amplified output power have also been presented. To our best knowledge, this is the highest energy extracted from the strictly all-fiber chirped pulse amplification system. The environmentally stable femtosecond laser source will find various applications in practice.